ACT001 improved cardiovascular function in septic mice by inhibiting the production of proinflammatory cytokines and the expression of JAK-STAT signaling pathway - Peng, Zhen; Lv, Xiaolong; Wang, Xintong; Shang, Ting; Chang, Jing; Salahdiin, Khalid; Guo, Yue; Zhang, Zhisen; Shen, Ru; Lyu, Ming; He, Shuang; Yang, Jian; et al. (Frontiers in Pharmacology, 2023)
Sepsis is a life-threatening multiple organ dysfunction syndrome (MODS) caused by a microbial infection that leads to high morbidity and mortality worldwide.Sepsis-induced cardiomyopathy (SIC) and coagulopathy promote the progression of adverse outcomes in sepsis. Here, we reported that ACT001, a modified compound of parthenolide, improved the survival of sepsis mice. In this work, we used cecal ligation and puncture (CLP) model to induce SIC. Transthoracic echocardiography and HE staining assays were adopted to evaluate the influence of ACT001 on sepsis-induced cardiac dysfunction. Our results showed that ACT001 significantly improved heart function and reduced cardiac pathology damage caused by sepsis.Coagulation accelerates organ damage in sepsis. We found that ACT001 decreased blood clotting in the FeCl3-induced carotid artery thrombosis experiment. ACT001 also reduced the production of neutrophil extracellular traps (NETs). RNA-sequencing of heart tissues revealed that ACT001 significantly down-regulated the expression of pro-inflammatory cytokines and the JAK-STAT signaling pathway. These results were confirmed with real-time PCR and ELISA. In summary, we found ACT001 rescued mice from septic shock by protecting the cardiovascular system. This was partially mediated by inhibiting pro-inflammatory cytokine production and down-regulating the JAK-STAT signaling.